2010
DOI: 10.1007/s00066-010-2105-6
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Bladder Volumes of Full Bladders in Definitive Radiotherapy for Cases of Localized Prostate Cancer

Abstract: We observed a significant decline in bladder volumes during the course of radiotherapy. The bladder volume at the pln-CT was a significant predictor of increased bladder volume variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 24 publications
2
30
1
Order By: Relevance
“…The reduction of bladder volume during the last two weeks of radiotherapy treatment could be due to patients becoming less attentive in the following bladder filling instructions towards the end of radiotherapy treatment or due to increased frequency of diarrhea which makes it difficult for patients to control micturition. Similar studies on bladder volume variation for prostate and cervix cancer patients reported a significant reduction in bladder volume [10], [11], [12] and [13]. Patients enrolled in all the above studies had larger mean bladder volume at CT-simulation compared to this study, ranging from 219 mL -378 mL It has been reported that maintaining consistency of large bladder volume throughout radiotherapy treatment is more difficult than smaller bladder volume.…”
Section: Bladder Volume Variationsupporting
confidence: 73%
See 1 more Smart Citation
“…The reduction of bladder volume during the last two weeks of radiotherapy treatment could be due to patients becoming less attentive in the following bladder filling instructions towards the end of radiotherapy treatment or due to increased frequency of diarrhea which makes it difficult for patients to control micturition. Similar studies on bladder volume variation for prostate and cervix cancer patients reported a significant reduction in bladder volume [10], [11], [12] and [13]. Patients enrolled in all the above studies had larger mean bladder volume at CT-simulation compared to this study, ranging from 219 mL -378 mL It has been reported that maintaining consistency of large bladder volume throughout radiotherapy treatment is more difficult than smaller bladder volume.…”
Section: Bladder Volume Variationsupporting
confidence: 73%
“…Most studies showed a reduction in the bladder volume towards the end of treatment particularly in prostate and cervical cancer [10], [11], [12] and [13]. Reduction or variation in bladder volume leads to the inconsistent amount of small bowel being irradiated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the prostate position can vary with respect to bone structures due to movements and physiological changes of internal organs [21] and/or of the target [27]. New localization techniques that rely on 3D soft-tissue imaging are required to improve imageguided radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…EPI suffers from the ability to accurately show interfraction movements [27]. It is well known that the interfraction reproducibility of prostate position is significantly affected by changes of rectum filling [29] and may be influenced, to a less extent [30], by the filling of the bladder [21]. Movements and physiological changes of internal organs and/or of the target make such an approach inaccurate in prostate radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Dawson et al [7] reported that even in this case the bladder volume is not constant during the treatment; the same observation was reported by Pinkawa et al [25]. O'Doherty et al [21] reported that patients informed to drink the same amount of liquid before every treatment are more able to maintain a constant bladder volume, although Nakamura et al [20] observed a significant decline in bladder volumes during the course of radiotherapy.…”
Section: Introductionmentioning
confidence: 53%